Express in simplest terms: `(x^2-2xy+y^2+x-y)/(x^2-y^2)`

1 Answer | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The expression `(x^2-2xy+y^2+x-y)/(x^2-y^2)` has to be simplified.

`(x^2-2xy+y^2+x-y)/(x^2-y^2)`

=> `((x - y)^2 - (x - y))/((x - y)(x + y))`

=> `((x - y)(x - y - 1))/((x - y)(x + y))`

=> `(x - y - 1)/(x + y)`

The expression `(x^2-2xy+y^2+x-y)/(x^2-y^2) = (x - y - 1)/(x + y)`

We’ve answered 318,913 questions. We can answer yours, too.

Ask a question